Early changes of ganglion cell-inner plexiform layer thickness and macular microvasculature in Posner-Schlossman syndrome: a binocular control study by OCTA - Hu, Zhiyi; Zhu, Liwei; Xu, Junli; Wei, Jiamin; Wu, Shuangqing; Dai, Qi; Xu, Qibin (Frontiers in Medicine, 2023)
To evaluate the early changes in ganglion cell-inner plexiform layer thickness and macular microvasculature in Posner-Schlossman syndrome (PSS) with a binocular control study involving optical coherence tomography angiography (OCTA). Twenty-six patients with unilateral PSS were included in this cross-sectional study. All subjects underwent a thorough ocular examination. Macular ganglion cell-inner plexiform layer (mGCIPL) and superficial macular microvasculature measurements, including vessel density (VD), perfusion density (PD) and the foveal avascular zone (FAZ), were recorded. In PSS-affected eyes, the mGCIPL thickness was significantly lower in all quadrants than in the contralateral eyes (all p < 0.05). Significant macular microvascular damage was found in the PSS-affected eyes, including whole-image VD (wiVD), wiPD, perifoveal VD (periVD) and periPD (all p < 0.05); but there was no obvious difference in parafoveal VD (paraVD), paraPD and FAZ parameters (all p > 0.05). In addition, a decreased wiVD and wiPD were significantly correlated with a smaller mGCIPL thickness and a decreased MD (all p < 0.05). These parameters may contribute to the early detection of glaucomatous damage and timely supervision of disease progression in PSS.